2023
DOI: 10.3389/fphar.2023.979111
|View full text |Cite
|
Sign up to set email alerts
|

Treatment attrition rates and relevant risk factors in multiple myeloma: A real-world study in China

Abstract: Background: For multiple myeloma (MM), the proportions of patients reaching the subsequent line of therapy (LOT) decline gradually and real-world data describing the attrition rates of LOT in Chinese MM were limited. Herein, we investigated the attrition rates by subsequent LOTs and their relevant risk factors in MM patients in China.Methods: MM patients who had been hospitalized and received at least one LOT from January 2008 to August 2019 in West China Hospital Sichuan University were retrospectively recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…They found that the DRd sequential pomalidomide/carfilzomib regimen as second-line therapy had the highest estimated 5-, 10-, and 15-year OS rates, and daratumumab-based regimen as the frontline therapy for TIE-NDMM had a more pronounced OS benefit than as second-line treatment ( 28 ). However, the study used combination attrition rates to estimate outcomes, which were variable factors in different studies ( 29 32 ). Further clinical studies are needed to validate the timing of daratumumab use.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the DRd sequential pomalidomide/carfilzomib regimen as second-line therapy had the highest estimated 5-, 10-, and 15-year OS rates, and daratumumab-based regimen as the frontline therapy for TIE-NDMM had a more pronounced OS benefit than as second-line treatment ( 28 ). However, the study used combination attrition rates to estimate outcomes, which were variable factors in different studies ( 29 32 ). Further clinical studies are needed to validate the timing of daratumumab use.…”
Section: Discussionmentioning
confidence: 99%